PERSEPSI MENTOR DAN MENTEE TENTANG PROGRAM MENTORSHIP - Grace Solely Houghty; Yakobus Siswadi (Fakultas Ilmu Keperawatan Universitas Advent Indonesia, 2015)
Evaluation in the first semester showed that there are 51 students of ETP batch 2013 who have to follow the matriculation program, seven students quitted the program, and five students from ETP batch 2014 were dropped out for violating academic rules. The mentorship program started in the Academic Year of 2013/2014 on its Even Semester. The evaluation for mentorship program has not been done within the Faculty of Nursing, Universitas Pelita Harapan. Objective: to identify the mentor’s and mentee’s perception about the mentorship program. Methods: The study design is descriptive quantitative study. The samples are 52 mentors and 314 mentees. The instrument is questionnaires in the form of self-report questionnaire. The data analyzed using the univariate method. Results: 38 mentors (73.08%) and 208 mentees (66.24%) that mentorship program can increase knowledge in learning, 29 mentors (55.77%) and 165 mentees (52.55%) agree that improve collaboration with others. 20 mentors (83.33%) and 85 mentees (88.54%) from 24 mentors and 96 mentees that intend to leave campus agree that mentorship program can increase influence to remain in on-campus accommodation. Discussions: It is expected that the mentorship program can be developed better, specifically for the mentor recruitment program and the ongoing training for mentors.